Estimating Firewater Runoff in Process Plants: an Analysis of Available Models for Retention Pond Sizing - Giuseppe Pino (Chemical Engineering Transactions)
The environmental impact of polluted firewater is a critical point to the current efforts to improve the sustainability of industrial plant. In case of a fire accidents in process plants, the firefighting water can cause considerable damages if it enters surface water, infiltrates the ground, or contaminates groundwater. By properly designing waste-water retention and treatment systems, these issues can be addressed taking into consideration the amount of contaminated firewater that needs to be collected and treated. This paper is a contribution to the estimation of amount of firewater runoff to be discharged in the drainage systems and the sizing of retention pond presenting the results of the application of different models and their convergence to a design value. Three models, based on object surface or the largest fire compartment area and selected from the European Safety guideline (UNECE, 2019), have been investigated. The analysis is, further, enhanced with two alternative calculation models that consider the contribution of the discharged firefighting foam extinguishing system.